Effects of Dizziness, Authenticity, and Satisfaction on Students’ Intention to Use VR in Vocational High School - Rahman, Muhammad Haristo; Mahmud, Amiruddin; Setialaksana, Wirawan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The study aims to identify the influence of variables such as dizziness, activity-related authenticity, object-related authenticity, and satisfaction on students' behavioural intentions to continue using Virtual Reality (VR) technology in a learning context. In this study, path analysis was employed to ascertain the impact of dizziness on satisfaction and behavioural intentions in VR technology users. The findings of the study demonstrate a substantial negative correlation between dizziness and satisfaction, indicating that an escalation in dizziness levels is concomitant with a decline in satisfaction and behavioural intention to persist in utilising VR. Furthermore, activity-related authenticity and object-related authenticity have been demonstrated to exert a significant positive influence on behavioural intention, thereby indicating that students are more inclined to continue utilising VR technology if they perceive the activities and objects within VR as more authentic. The study also found that student satisfaction is the strongest factor in increasing behavioural intention to continue using VR, with path coefficients indicating a significant positive influence. The findings of this study provide important insights into the factors influencing students' behavioural intentions to continue using VR in learning. Consequently, it is anticipated that this study will contribute to the development and application of VR technology in the domain of vocational education. Moreover, it is expected to provide recommendations for technology developers and educators to design more effective and enjoyable learning experiences, taking into account the physical comfort and authenticity of the VR content used.